Tunable transport characteristics of double-gated graphene field-effect transistors using P(VDF-TrFE) ferroelectric gating. (January 2016) - Sun, Yi-Lin; Xie, Dan; Xu, Jian-Long; Li, Xin-Ming; Zhang, Cheng; Dai, Rui-Xuan; Li, Xian; Meng, Xiang-Jian; Zhu, Hong-Wei
Abstract: Double-gated graphene field effect transistors (GFETs) have been fabricated using the graphene grown by CVD method as channel conductor and the organic ferroelectric P(VDF-TrFE) film spin-coated as top gate insulator. An interesting method for efficiently modulating the charge transport characteristics of graphene films by introducing double-gated graphene field-effect transistor structure and organic ferroelectric P(VDF-TrFE) as top gate dielectrics has been reported. The introduction of functional P(VDF-TrFE) gate dielectric is to modulate the charge transport characteristics of graphene by polarization doping effects, which provides us an alternative method to rule out the environmental effects on graphene and obtain the GFETs with improved performances. Moreover, bottom gating induced electrostatic doping effects are also found to be an effective way to highly control the top gated transfer characteristics of GFETs.